First, calculate the amount of increase the employee will receive in the first year: $65,000 * 3% = $<<65000*3*.01=1950>>1,950
Then calculate the employee's salary after one year: $65,000 + $1,950 = $<<65000+1950=66950>>66,950
Then calculate the amount of increase the employee will receive in the second year: $66,950 * 3% = $<<66950*3*.01=2008.5>>2,008.5
Then calculate the employee's salary after two years: $66,950 + $2,008.5 = $<<66950+2008.5=68958.5>>68,958.5. Answer: \boxed{68,958.5}.
An employee is starting a job with an annual salary of $65,000. The employee’s annual salary will increase by 3% at the end of each increase by 3% at the end of each year with the company. What will the employee’s annual salary, in dollars, be at the end of the second year with the company?(1 point)
1 answer